Soil seed bank of plant species as a function of long-term soil management and sampled depth Banco de sementes de espécies vegetais em função de distintos manejos do solo por longo período e profundidade amostrada - G Concenço (Planta Daninha, 2011)
This study aimed at assessing the level of weed infestation indifferent areas that were submitted to different soil management for 16 years. Four management systems were studied: (1) agriculture only under conventional tillage system; (2) agriculture only under no-till system; (3) crop-livestock integrationcrop-livestock integration; (4) livestock only. These areas were sampled at three soil depths (0-5, 5-10 and 10-15 cm), and soil was stored in plastic pots and taken to a greenhouse, where soil moisture and weight were standardized. Soil was kept near 70% moisture field capacity, being revolved every 20 days when all seedling emerged from soil were counted, identified and collected for dry mass assessment. The soil coverage by weeds, number of weed seedlings and dry mass of the weedy community were assessed. A phytoecological analysis was conducted. Weed composition is differentdifferent among management systems after 16 years. Areas with livestock showed much smaller number of weed species in comparison to systems where only grain crops are grown. The presence of livestock affects the potential of germination of soil seed bank. Agriculture systems are similar in terms of weed composition along soil profile, while systems involving livestock show little relation in what regards such sampled depths. Conservationist models of land exploration contribute to reduce severity of weed species occurrence in the long term. Objetivou-se avaliar o nível de infestação por plantas daninhas em áreas submetidas a manejos distintos por 16 anos: (1) agricultura em sistema convencional de preparo; (2) agricultura em sistema plantio direto; (3) integração lavoura/pecuária; (4) somente pecuária. Amostras de solos destas áreas foram coletadas em três profundidades (0-5, 5-10 and 10-15 cm), depositadas em potes plásticos e levadas a casa de vegetação. O solo era revolvido a cada 20 dias, quando as plantas daninhas presentes eram identificadas e coletadas. Foram avaliados cobertura por plantas daninhas; densidade de plantas daninhas e massa seca da comunidade infestante. Foi também conduzida análise fitoecológica em função dos distintos manejos e profundidades. Áreas onde pastagens estiveram presentes tiveram menor infestação por plantas daninhas que áreas onde somente agricultura era utilizada. A composição florística difere entre sistemas de manejo. Áreas onde a pecuária está presente apresentaram número de plântulas de espécies daninhas muito inferior a sistemas onde somente agricultura está presente. A presença de criação de gado afeta o potencial de emergência das espécies presentes no banco de sementes do solo. Sistemas de agricultura sem integração apresentam alta similaridade em termos de composição de espécies ao longo do perfil do solo enquanto sistemas integrados com pecuária apresentam pouca relação entre as profundidades amostradas. Modelos conservacionistas de exploração do solo contribuem com a redução da severidade de ocorrência de espécies daninhas a longo prazo.